Legal Certainty Regarding the Rules for Qualifying Unlawful Acts and Defaults in the Framework of Civil Law Reform in Indonesia - Juang, Nurhadi Ahmad; Kaban, Maria; Sembiring, Rosnidar (Research Horizon, 2025)
Various phenomena have emerged at the level of the practice of resolving Unlawful Acts and Defaults cases through litigation in court which have also attracted attention for research. Most studies discuss the merging and separation of Unlawful Acts and Defaults lawsuits in court. However, research that tries to criticize and offer a new concept of the rules on Unlawful Acts and Defaults in order to realize legal reform that provides certainty has not been widely carried out. This study will discuss how the concept of Unlawful Acts and Defaults in positive law in Indonesia, how to qualify it, and what are the weaknesses of the current rules. The study adopts normative legal research, also known as doctrinal legal research, supplemented by interviews with Judges from the Medan District Court and Advocates, using interview guidelines as a data collection tool. The results of the study indicate that the concept of rules in qualifying Unlawful Acts and Defaults in Indonesia is currently considered unable to realize legal certainty. Therefore, it is necessary to update the Civil Law regarding the rules for qualifying Unlawful Acts and Defaults in Indonesia which can create legal certainty.